Panel Analysis of Relationship Between Sales and Profitability of Crop Production Companies in the Republic of Serbia - Dakić Stojanka; Nuševa Daniela; Peštović Kristina; Ilić Teodora; Tica Nedeljko; Jakšić Dejan (Contemporary Agriculture)
This paper presents the research on factors influencing profitability of crop production companies in the Republic of Serbia. The research is based on 416 observations of financial statements of crop production companies during the period 2008–2023. The analysis was conducted using panel data models. Profitability was measured by return on assets, while the independent factors examined included: size, leverage, sales growth and current ratio. The findings reveal that although crop production companies in the Republic of Serbia have an average positive profitability rate, the level remains low. Furthermore, the results indicate that sales growth has a positive and significant impact on profitability, while the current ratio and size have a negative and significant effect. The results of the study are significant for a wide range of stakeholders, including managers, owners and regulatory bodies, as the results indicate the profile of crop production companies that can be used for improving profitability and fostering sustainable growth and development.